Gender differences in mental well-being: A decomposition analysis - David Madden (University College Dublin, UCD School of Economics, 2008)
The General Health Questionnaire (GHQ) is frequently used as a measure of mental well-being. A consistent pattern across countries is that women report lower levels of mental well-being, as measured by the GHQ. This paper applies decomposition techniques to Irish data for 1994 and 2000 to examine the factors lying behind the gender differences in GHQ score. For 1994 most of the difference is accounted for by characteristics while in 2000 most of the difference arises from returns to characteristics. The issue of path dependence, or choice of reference group, is shown to be important, mostly arising from the differing effect of principal economic status on men and women.
hdl:10197/765
Keywords: I12; I31; I32; 330; GHQ; decomposition; path dependence